2014
DOI: 10.1161/circresaha.114.302745
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Plaques to Predict and Better Manage Patients With Acute Coronary Events

Abstract: Culprit lesions of patients who have had an acute coronary syndrome commonly are ruptured coronary plaques with superimposed thrombus. The precursor of such lesions is an inflamed thin-capped fibroatheroma. These plaques can be imaged by means of invasive techniques such as intravascular ultrasound (and derived techniques), optical coherence tomography and near-infrared spectroscopy. Very often these patients exhibit similar (multiple) plaques beyond the culprit lesion. These remote plaques can be assessed non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 88 publications
0
24
0
Order By: Relevance
“…6K). Thus, we showed that Glut1 connects the enhanced glucose uptake in atheromatous plaques of ApoE −/− mice, 2730 with their myelopoiesis through regulation of HSPC maintenance and myelomonocytic fate.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…6K). Thus, we showed that Glut1 connects the enhanced glucose uptake in atheromatous plaques of ApoE −/− mice, 2730 with their myelopoiesis through regulation of HSPC maintenance and myelomonocytic fate.…”
Section: Resultsmentioning
confidence: 77%
“…2730 However, a recent study has called into question the relevance of these observations, as macrophage-specific overexpression of Glut1 did not aggravate atherosclerosis in mice compared to Glut1 sufficient controls, 46 reflecting the need for a better understanding of the underlying mechanisms. Our study provides direct evidence that Glut1 connects the enhanced glucose uptake in atheromatous plaques of ApoE −/− mice with their myelopoiesis through Glut1-dependent regulation of HSPC maintenance and myelomonocytic fate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, imaging can report on stromal immune cell activity in multiple tissues in living patients. In addition to coronary imaging (recently reviewed elsewhere (41)), as comorbidities aggravate cardiovascular disease via inflammatory crosstalk, noncardiovascular organs may also be of interest and therefore constitute another putative therapeutic target. To understand systems-wide immune action after MI, particularly connections of cardiovascular with immune and hematopoietic organs, future imaging studies should focus not only on the ischemic heart, but also on remote myocardium, local lymph nodes, nonculprit atherosclerotic lesions, spleen, and bone marrow, and integrate these data with analysis of blood.…”
Section: Chances and Challengesmentioning
confidence: 99%
“…43 However, because of increased noise and artifacts, image interpretation can be difficult; furthermore, IVUS has insufficient spatial resolution to reliably and reproducibly detect thin fibrous cap. 44 OCT uses near infrared light (1.3 μm wavelength) emitted through a fiberoptic wire with rotating lens to achieve exceptionally high spatial resolution (10-15 μm), providing accurate measurement of fibrous cap thickness with strong correlation to histology, 45 and good sensitivity and specificity to distinguish plaque type. 46 However, correct differentiation between calcium and lipid pool can be challenging with OCT, and its limited tissue penetration (1-3 mm) makes assessment of the entire plaque volume impossible.…”
Section: Intravascular Coronary Imagingmentioning
confidence: 99%